Scientific work of the department of theoretical and Slavic linguistics - Barkovich, Aliaksandr A.; Kozlovskaya, Lyudmila A.; Bobko, Tatyana V. (Journal of the Belarusian State University. Philology, 2024)
The scientific achievements of the department of theoretical and Slavic linguistics of the faculty of philology of the Belarusian State University are summarised. It has been proven that for more than 50 years the department has been one of the leading structural units of the university, and its staff conducts the study of theoretical aspects of linguistics and Slavic studies at a high professional level. It is confirmed that nowadays, following the rich traditions enshrined in the achievements of its own school, the department is actively working in prospective interdisciplinary scientific areas, including the field of digital philology.